Mechanical characterization of oligo(ethylene glycol)-based hydrogels by dynamic nanoindentation experiments. (June 2015) - Guglielmi, P.O.; Herbert, E.G.; Tartivel, L.; Behl, M.; Lendlein, A.; Huber, N.; Lilleodden, E.T.
Abstract: Oligo(ethylene glycol)-based (OEG) hydrogel samples of varying cross-link densities and degrees of swelling were characterized through dynamic nanoindentation testing. Experiments were performed using a non-standard nanoindentation method, which was validated on a standard polystyrene sample. This method maximizes the capability of the instrument to measure the stiffness and damping of highly compliant, viscoelastic materials. Experiments were performed over the frequency range of 1 to 50 Hz, using a 1 mm diameter flat punch indenter. A hydration method was adopted to avoid sample dehydration during testing. Values of storage modulus ( E ′ ) ranged from 3.5 to 8.9 MPa for the different OEG-hydrogel samples investigated. Samples with higher OEG concentrations showed greater scatter in the modulus measurements and it is attributed to inhomogeneities in these materials. The ( E ′ ) values did not show a strong variation over frequency for any of the samples. Values of loss modulus ( E ″ ) were two orders of magnitude lower than the storage modulus, resulting in very low values of loss factor ( E ″ / E ′ <0.1). These are characteristics of strong gels, which present negligible viscous properties.